Spatial and Temporal distribution of Waterborne Diseases in Namanyonyi Sub-County, Mbale District, Uganda (International Journal of Scientific Research and Management (IJSRM), 2016)
Waterborne disease is of great concern all over the world. Waterborne diseases represent significant burden of diseases in the globe. Nearly 4% of diseases are attributable to water, sanitation and hygiene, and approximately 2.2 million people die every year due to diarrheal diseases worldwide. The purpose of this study was to investigate the spatial and temporal distribution of waterborne diseases in Namanyonyi Sub County. Retrospective records from Namanyonyi Health Centre III were reviewed to determine the prevalence of waterborne diseases from January to December 2010-2014. Data was analysed with the help of SPSS and Microsoft excel. The results show that Diarrhea is the most prevalent among the waterborne diseases (33.5%) and cholera was the least (3.0%). The more frequent age group (52.6%) was 0-5 years and females (58.1%) are more prone to waterborne diseases in the study area. The ANOVA output indicates that there is significant difference between the different age groups (P=0.001). In other hand waterborne diseases were mostly prevalent in rainy season than dry season, showing cases of 1188 and 992 respectively. The study recommends improvement in hygienic conditions, treatment of dug wells and boreholes and adaptation of waste management strategies